(untitled) (Research, Society and Development, 2019)
The main factor in the training process is the articulation of theory and practice, evidencing whether the student’s learning was significant and generated the necessary skills in the labor market, which is increasingly demanding and competitive. The present text aims to make theoretical notes about the profile of the tutor in the subjects of supervised curricular internship in the course of Pedagogy in the distance modality. To reach the proposed objectives, the methodology used was of a qualitative nature, with the use of the bibliographic review. As results, the importance of the supervised internship in the life of the student is revealed, so that they understand the future field of professional performance.